Low-energy-consumption efficient synergistic carbon dioxide absorbent and preparation method thereof
Through the synergistic combination of hydroxyethylethylenediamine, amino functionalized ionic liquid and catalyst, the existing carbon dioxide absorber has high energy consumption, small absorption and low desorption efficiency, and low energy consumption and high efficiency carbon dioxide absorption and desorption are achieved, which improves circulation and regeneration performance and simplifies the process.
Patent Information
- Application Number
- CN202510116485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
AI Technical Summary
The existing carbon dioxide absorbers have problems such as high energy consumption, small absorption, low desorption efficiency, poor circulation stability and cumbersome synthesis process.
The synergistic combination of hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst is adopted to increase the absorption, desorption amount and desorption rate of carbon dioxide while reducing energy consumption and viscosity by adjusting its weight percentage.
It achieves low energy consumption and efficient carbon dioxide absorption and desorption, improves the circulation and regeneration performance of absorbents, and simplifies raw materials and synthesis processes.
Smart Images

Figure CN119793149A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dioxide absorption and capture, and specifically relates to a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent and a preparation method thereof. Background Art
[0002] Carbon capture, utilization and storage technology plays a vital role in global climate change mitigation and effective control of carbon dioxide emissions. This technical path aims to capture carbon dioxide from large flue gas emission sources, such as coal-fired power plants and cement plants, and prevent it from entering the atmosphere through utilization or long-term storage, thereby reducing the accumulation of greenhouse gases. However, despite its widely recognized strategic value, the practical application of carbon capture, utilization and storage technology still faces many challenges, especially in the key link, namely the carbon dioxide capture stage, and the development of efficient and economically viable absorbents is particularly urgent.
[0003] At present, the main carbon dioxide absorbents are alcoholamine absorbents such as ethanolamine and diethanolamine. Although they have been widely used in commercial-scale carbon dioxide capture devices, they have obvious limitations. Although alcoholamine absorbents have a high affinity for carbon dioxide, they have poor stability and are prone to degradation under actual use conditions, resulting in a decrease in absorption effect. There are problems such as small absorption capacity, low desorption rate, poor cycle stability, complex synthetic raw materials and cumbersome synthetic process. In both documents 1 "Evaluating CO2-Desorption Performance of Solid Acid Catalysts in CO2-Loaded Aqueous Solutions of N-Ethylethanolamine" (Hitesh D. Rawate and Prakash D. Vaidya. Ind. Eng. Chem. Res. 2023, 62, 9787-9796.) and 2 "Experimental investigation on post-combustion CO2 capture for [Bpy] [NO3] and MEA aqueous blends with lower regeneration energy" (Yinge Bai a, b, Kaixuan Wang a, Lulu Wang a, Shaojuan Zeng a, Lu Bai a, Xiangping Zhang. Separation and Purification Technology 327 (2023) 124846.), it is mentioned that amine absorbents have the problem of high energy consumption.
[0004] In document 3, "Development and performance research of two-phase absorbent for carbon capture of coal-fired flue gas" (Zhang Qiyue, Fang Mengxiang, Zhou Kang, et al. Thermal Power Generation, 2023, 52(04): 24-33.), ethanolamine and hydroxyethylethylenediamine diamine are used as the main absorbent, and diethylene glycol dimethyl ether is used as the phase separator to achieve the purpose of phase change stratification after absorption. However, there are deficiencies in the absorption principle and formula structure.
[0005] In document 4 "Efficient CO2absorption in aqueous dual functionalized cyclicionic liquids" (TiwariS C, Pant KK, Upadhyayula S. Journal of CO2Utilization, 2021, 45: 101416), four functionalized ionic liquids were synthesized in the system, and their saturated carbon dioxide absorption was experimentally determined to be higher than that of monoethanolamine solution. The ionic liquid uses the long-chain olefin triethylenetetramine as a cation, and because it has more amino groups on it, it has a higher carbon dioxide absorption capacity. However, since long-chain olefins are prone to bond breaking in high temperature environments, the stability of the system is poor.
[0006] Reference 5 "Efficient CO2 capture by a novel two-phase absorbent-ionic liquid system" (Lü Chao, Zhang Xiwen, Jin Lijian, et al. Chemical Industry Progress, 2023, 42(06): 3226-3232.) uses ethanolamine, hydroxyethylethylenediamine, triethylenetetramine and diethylenetriamine (DETA) as main absorbents, tetramethylethylenediamine as phase separator, and 1,8-diazabicyclo[5.4.0]undec-7-ene-imidazole ionic liquid to increase the carbon dioxide absorption load. Although ionic liquids help to increase the CO2 absorption load of the system, the viscosity of the system generally exceeds 150 mPa·s.
[0007] Reference 6 "Mechanism of CO2 capture by amino-azole bifunctional ionic liquid phase change absorbent" (Lü Bihong, Zhan Xiaohui, Li Xin, et al. Chinese Science: Chemistry, 2021, 51(12): 1660-1670.) is composed of a synthetic diethylenetriamine imidazole functionalized ionic liquid dissolved in an ethanol-water mixed solvent. It is a homogeneous solution before absorbing carbon dioxide, and a liquid-liquid phase transition occurs after absorption saturation.
[0008] In reference 7, "Design of Ionic Liquid Composite Solvents and Study on CO2 Capture Performance" (Wang Kaixuan. Zhengzhou University, 2022.), superbase functionalized ionic liquids and conventional ionic liquids were respectively compounded with ethanolamine to obtain two ionic liquid-ethanolamine composite systems with traditional ethanolamine aqueous solution as the main absorbent. Since the main absorbent is still ethanolamine solution, it cannot completely get rid of the limitations of the traditional ethanolamine system.
[0009] In the Chinese invention patent entitled "A polyamine functionalized ionic liquid, its preparation method and application", publication number: CN115945034A, after the ionic liquid is used as the main absorbent and then formed into a composite system with ethylene glycol and diethylene glycol dimethyl ether, it has better absorption efficiency and lower regeneration energy consumption than the traditional ethanolamine aqueous solution, but its viscosity is higher.
[0010] The Chinese invention patent entitled "An amino-functionalized ionic liquid-alcoholamine composite absorbent for CO2 capture and its preparation method", publication number: CN119258727A discloses a composite absorbent prepared from main absorbent alkanolamine, absorption promoter amino-functionalized ionic liquid and water, but still has problems such as high energy consumption, low desorption rate and the lack of synergistic effect in the system.
[0011] It can be seen from the above records that the currently available amine alcohol dioxide absorbents still have obvious problems such as high energy consumption, small absorption capacity, low desorption efficiency, and high viscosity. Summary of the invention
[0012] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent and a preparation method thereof, so that the absorbent has the characteristics of low energy consumption, large absorption capacity, high desorption efficiency, good recycling performance, simple raw materials and synthesis process, etc.
[0013] The technical solution adopted by the present invention to solve the technical problem is: the low-energy consumption and high-efficiency synergistic carbon dioxide absorbent comprises the following components: 4.5-7.5g of hydroxyethylethylenediamine, 1.5-4.5g of amino-functionalized ionic liquid, 0.015-0.06g of catalyst and water.
[0014] The weight percentages of the hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst are 15-25%: 5-15%: 0.005-0.02%. Preferably, the weight percentages of the hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst are 20%: 10%: 0.01%.
[0015] The applicant has found through repeated experiments that the weight percentage of hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst is in the range of 15-25%: 5-15%: 0.005-0.02% to ensure that it has a higher absorption amount, desorption amount and desorption rate; as well as lower viscosity and energy consumption.
[0016] Hydroxyethylethylenediamine (AEEA for short) is the main absorbent, and its properties are stable; the amino-functionalized ionic liquid (DETAH [Pz] or TETAH [Pz] for short) in the present application.
[0017] Hydroxyethylethylenediamine can increase the absorption rate and amount of carbon dioxide, but adding too much hydroxyethylethylenediamine will lead to side reactions, degradation or formation of unstable compounds, which will ultimately affect its stability and regeneration performance. Adding too little hydroxyethylethylenediamine will reduce the absorption amount and absorption rate of carbon dioxide. Adding too much amino-functionalized ionic liquid will increase viscosity and high energy consumption; adding too little amino-functionalized ionic liquid will reduce the absorption amount and absorption rate of carbon dioxide. Adding too much catalyst will reduce fluidity and increase the probability of equipment damage. Due to kinetic limitations, too much catalyst cannot further improve the catalytic efficiency. Adding too little catalyst will reduce the rate of the catalytic reaction and reduce the conversion efficiency of carbon dioxide.
[0018] AEEA, amino-functionalized ionic liquid and catalyst work together to capture carbon dioxide, which is manifested as a collaborative absorption process and a collaborative desorption process. The capture includes two processes: absorption and desorption. Taking the collaborative absorption and desorption process of AEEA, [DETAH][Pz] and catalyst as an example, the principle is as follows:
[0019] AEEA, [DETAH][Pz] and catalyst synergistic absorption process: During the carbon dioxide absorption process, the primary and secondary amine groups of AEEA first react with carbon dioxide to form carbamates. As the reaction proceeds, these carbamates are gradually hydrolyzed and converted into bicarbonate and carbonate ions. In this process, the cation [DETAH] in [DETAH][Pz] + and anion [Pz] - It also participates in the reaction through the zwitterion mechanism, providing additional reactivity, which helps to slow down the decrease in the absorption rate of AEEA due to reaction consumption, and promotes the hydrolysis of carbamate to generate more carbonate and bicarbonate, thereby improving the carbon dioxide absorption capacity of the system. In the process of carbon dioxide absorption, [Pz] - The anion generated by the dissociation of [DETAH][Pz] is protonated, causing its C7 NMR resonance peak to move from δ = 44.79 ppm to δ = 42.55 ppm. This indicates that during the carbon dioxide absorption process, [Pz]- When reacting with carbon dioxide, protonation occurs, further promoting the absorption process.
[0020] The catalyst plays a key role in this process. The Brønsted acid sites BASs on its surface act as proton donors, providing a large number of protons H + These protons play a vital role in the carbon dioxide capture reaction. The protons act on the zwitterion intermediates generated by the reaction of AEEA and carbon dioxide. Under the action of the protons, the carboxylate ions COO - The carbonyl carbon atom of the carbonyl is attacked, resulting in the breaking of the carbon-nitrogen bond, which in turn forms carboxylic acid and amine compounds. This process converts the unstable carbamate intermediate into a more stable carboxylic acid product, while releasing amine compounds, which promotes the process of carbon dioxide absorption.
[0021] In addition, the presence of protons on the catalyst surface not only accelerates the reaction rate of carbon dioxide and amine compounds to form more carbamates, but also improves the reaction efficiency, allowing carbon dioxide to be captured and absorbed more efficiently.
[0022] AEEA, [DETAH][Pz] and catalyst synergistic desorption process: During the desorption process, the BASs of the catalyst continue to play an important role. They provide protons H + , promoting urethane RN + -COO - At the same time, these protons also pass through the active site B of BASs. - From the protonated amine RNH3 + In addition, the low acid sites of the catalyst, LASs, act as proton acceptors and can obtain acidic protons from the protonated amine RNH3 + The protons are received by the amine RNH2, and these protons are transferred to the water phase, further accelerating the desorption process. At the same time, the protonated piperazine anion promotes the desorption of RN in the presence of the catalyst. + -COO - decomposition, while ensuring that AEEA and [DETAH] + regeneration.
[0023] Preferably, the catalyst is nano-silicon dioxide, nano-titanium dioxide, activated carbon or zeolite molecular sieve.
[0024] The desorption of carbon dioxide is also the process of amine regeneration. The above four types of catalysts are solid acid catalysts, which are referred to as SACs. Based on the zwitterion principle, the carbon dioxide desorption process under non-catalytic conditions mainly includes two steps: one is carbamate AmineCOO -The first is the cleavage of the CN bond, and the second is the protonated amine AmineH2 + The two specific reaction processes are as follows:
[0025] 1. Breaking of CN bonds in carbamates: This is an endothermic reaction that mainly depends on the transfer of acidic protons; in this process, after the carbamate molecules absorb heat, the CN bonds become unstable and break.
[0026] 2. Rapid proton transfer: protonated amine AmineH2 + The protons in the desorption process are transferred rapidly; this process can provide the acidic protons required for the decomposition of carbamates. However, the desorption of carbon dioxide is a highly endothermic reaction, and in alkaline solutions, amines are Brønsted bases with a stronger proton-accepting ability than water, which limits the ability of amines to promote protons from AmineH2 + The ability to transfer.
[0027] In the Bronsted acid-base theory, a base is defined as a substance that can accept a proton, while an acid is defined as a substance that can donate a proton. In alkaline solutions, amines are Bronsted bases. In alkaline solutions, amines have a stronger ability to accept protons than water. Therefore, when the protonated amine AmineH2 + When it exists, it tends to remain in a protonated state rather than releasing protons, making the protonated amine formed after accepting protons relatively stable and hindering the transfer of protons from the protonated amine to other molecules or ions, thereby affecting the desorption rate of carbon dioxide.
[0028] Bicarbonate ions can act as proton acceptors, thereby reducing the activation energy of the deprotonation reaction, but in the carbon dioxide-rich phase, the absorbent contains only a small amount of bicarbonate ion groups. Therefore, this leads to a relatively low desorption rate in the carbon dioxide desorption process. At the same time, in order to achieve effective desorption at a higher desorption temperature, more energy is required. The chemical reaction formula is as follows:
[0029]
[0030] SACs exist Acid sites, abbreviated as BASs, such as -OH, -SO3H, and -HPO3, can effectively act as proton donors, thereby accelerating the proton transfer process in CO2-loaded solvents. On the other hand, Lewis acid sites in SACs, abbreviated as LASs, such as unsaturated Co, Fe, and Zr sites, can effectively act as proton donors, thereby accelerating the proton transfer process in CO2-loaded solvents. - The electron acceptors of N and O atoms in the NH4COO4 can catalyze the breaking of NC bonds, further improving the -Therefore, the presence of these acid sites can endow the amine solvent with a higher carbon dioxide desorption rate, which reduces steam consumption and operating costs by reducing liquid circulation.
[0031] There are two types of amino groups in AEEA, primary amine groups and secondary amine groups. The primary amine groups react with carbon dioxide first, and the carbon dioxide molecules are connected to the primary amines to form carbamates, which are AEEA-COO P - , the carbon dioxide molecule is attached to the secondary amine to form a carbamate AEEA-COO s - The specific molecular structure formed can be found in Fig. 9 (c) Points 8 and 9.
[0032] In the initial stage of carbon dioxide absorption, carbamate is formed on the primary and secondary amine functional groups of AEEA:
[0033]
[0034] As AEEA is consumed, [DETAH][Pz] gradually begins to participate in the reaction, which can slow down the decline in absorption rate:
[0035]
[0036] The Brønsted acid sites BASs on the catalyst surface act as proton donors, providing a large number of free protons H + , which promotes the conversion of carbamates into aminocarboxylic acids and accelerates the absorption process of CO2.
[0037]
[0038] As the reaction proceeds, the carbon dioxide in the solution increases and the absorbed product is hydrolyzed to form bicarbonate and carbonate:
[0039]
[0040] The carbon dioxide desorption process mainly includes three key steps: the decomposition of bicarbonate and carbonate, RN + -COO - Decomposition and RNH3 + In the whole process, the catalyst plays an important role by utilizing its dual characteristics of BASs and LASs.
[0041] BASs on the catalyst surface act as proton donors HB, directly providing a large number of free protons H + , promote RN + -COO -Converted to RN-COOH. At the same time, the catalyst provides proton active sites B - From RNH3 + Obtain acidic protons from the
[0042]
[0043] LASs on the catalyst surface act as proton acceptors - , from RNH3 + accepts a proton, thereby converting RNH3 + converted into RNH2; at the same time, these protons are transferred to water, promoting the acceleration of the desorption process.
[0044]
[0045] In addition, the abundant BASs on the catalysts can donate protons, which react with bicarbonate and carbonate to generate carbon dioxide.
[0046]
[0047] At the same time, the protonated piperazine anion [Pz]-H promotes the RN + -COO - Decomposition of AEEA, [DETAH] + regeneration, thus ensuring high absorption capacity and high desorption rate of [DETAH][Pz] solution.
[0048]
[0049] Nano silicon dioxide has the advantages of high specific surface area and surface activity, good dispersibility, high light stability, low cost and high catalytic activity, non-toxicity and environmental protection. Nano titanium dioxide has the advantages of high catalytic efficiency, environmental safety, reusability, high chemical stability, non-toxicity, strong antibacterial and deodorizing ability. Activated carbon is referred to as AC. AC has the advantages of large specific surface area, developed pore structure, adjustable surface chemical properties, low price, acid and alkali resistance and good ion exchange capacity. Zeolite molecular sieve has the advantages of high specific surface area, controllable pore size, strong absorption capacity, and good chemical and thermal stability.
[0050] Preferably, the catalyst is H-MOR, H-ZSM-5, HY or SAPO-34 zeolite molecular sieve; Structural characteristics of zeolite molecular sieve: the lattice framework of zeolite molecular sieve is mainly composed of silicic acid and has a highly regular pore and chamber structure. The pore size is related to the type of cation.
[0051] H-MOR molecular sieve is obtained by replacing the cations in mordenite with hydrogen ions through the ion exchange method; H-MOR can maintain stable structure and performance under high temperature and high pressure conditions.
[0052] HY can optimize the selectivity of catalytic cracking products by adjusting the silicon-aluminum ratio and pore size distribution, thereby improving the yield and quality. The porous structure makes it an ideal material for gas separation, and can be used to remove or recover harmful substances in industrial waste gas to reduce environmental pollution. It can exchange with cations in water, thereby removing impurities and harmful substances in water and improving water quality.
[0053] SAPO-34 has a unique pore structure, excellent chemical stability, good thermal stability and hydrothermal stability. By adjusting its composition and preparation conditions, it can be controlled to exhibit appropriate acid strength in catalytic reactions.
[0054] H-ZSM-5 has high catalytic activity, high selectivity, high thermal stability and acid resistance, and an adjustable silicon-aluminum ratio. H-ZSM-5 is an inorganic structural material with a regularly arranged cavity inside a macromolecule, and has a large number of sieve holes and micropores inside. The silicon-aluminum ratio of H-ZSM-5 will directly affect its absorption performance, which is specifically manifested in the absorption capacity and absorption rate. When the silicon-aluminum ratio increases, the positive charge in the molecular sieve decreases, and the absorption capacity will also decrease. For molecular sieves with the same pore size and morphology, the lower the silicon-aluminum ratio, the stronger the absorption performance; the structure of H-ZSM-5 will affect the speed of molecular entry and diffusion, so the silicon-aluminum ratio also affects the absorption rate of molecules. In molecular sieves with a higher silicon-aluminum ratio, the diffusion rate of molecules in the pores will decrease due to the large number of pore branches, resulting in a slower absorption rate. H-ZSM-5 has a relatively low silicon-aluminum ratio and has good active centers, so it has good absorption capacity. The silicon-aluminum ratio of H-ZSM-5 is 27, and it is referred to as H-ZSM-5 (27) in this application. The silicon-to-aluminum ratio of H-ZSM-5 is 46, which is referred to as H-ZSM-5 (46) in this application. Preferably, the silicon-to-aluminum ratio of H-ZSM-5 is 21, which is referred to as H-ZSM-5 (21) in this application.
[0055] More preferably, the catalyst is a zeolite molecular sieve with a silicon-aluminum ratio of 0.5 to 80; the silicon-aluminum ratio refers to the molar ratio of silicon dioxide to aluminum oxide. The silicon-aluminum ratio is an important factor in evaluating the structure of the zeolite molecular sieve. Different silicon-aluminum ratios and preparation conditions will affect its structural characteristics, which can ensure that the catalyst is both active and highly stable.
[0056] The present invention also provides a method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent, comprising the following steps:
[0057] (1) reacting 0.82-2.45 g of an organic amine compound, 0.68-2.05 g of piperazine, 16-40 g of ethanol and 4-10 g of water to obtain component A;
[0058] (2) distilling component A under reduced pressure and drying to obtain an amino-functionalized ionic liquid;
[0059] (3) The amino-functionalized ionic liquid obtained in step (2), hydroxyethylethylenediamine, a catalyst and water are mixed and ultrasonically dispersed to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber.
[0060] The reaction conditions of step (1) are as follows: temperature of 25-40° C., rotation speed of 400-800 rpm, and reaction time of 24-36 h; the temperature of reduced pressure distillation of step (2) is 60-70° C., and the time is 3-4 h; the reduced pressure distillation is performed by a rotary evaporator; the drying is performed by a vacuum drying oven; the ultrasonic dispersion of step (3) is performed for 6-10 min; and the ultrasonic dispersion is performed by an ultrasonic cleaning machine.
[0061] As the temperature rises, the density of the low-energy and high-efficiency synergistic carbon dioxide absorber decreases. This is because the average kinetic energy of the molecules in the solution increases, which weakens the interaction between molecules and increases the average distance between molecules, thereby reducing the number of molecules per unit volume. The final result is a decrease in its density.
[0062] The organic amine compound is diethylenetriamine or triethylenetetramine; diethylenetriamine is referred to as DETA, and triethylenetetramine is referred to as TETA. The higher the concentration of the organic amine, the higher the carbon dioxide absorption capacity will be. However, the increase in amine concentration will lead to an increase in solution viscosity, a decrease in mass transfer efficiency and an increase in cost. At present, the most basic absorbent in the organic amine chemical absorption method is a 30wt% ethanolamine aqueous solution, which is the earliest carbon dioxide absorbent used and is also the benchmark for evaluating the performance of other absorbents. At the same time, this concentration is also an absorbent concentration suitable for capturing low-concentration flue gas carbon dioxide. The weight percentage of hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst is 20%:10%:0.01%, which has the best absorption-desorption performance.
[0063] When the organic amine compound is diethylenetriamine, the chemical reaction formula of step (1) is: The amino-functionalized ionic liquid obtained in step (2) is [DETAH][Pz].
[0064] When the organic amine compound is triethylenetetramine, the chemical reaction formula of step (1) is:
[0065] The amino-functionalized ionic liquid obtained in step (2) is [TETAH][Pz].
[0066] The temperature of the vacuum distillation is 60-70°C, and the time of the vacuum distillation is 3-4 hours. Step (2) vacuum distillation removes unreacted raw materials and excess solvent; the vacuum distillation temperature is 60-70°C to avoid ethanol decomposition and vaporization. Within this temperature range, ethanol will not decompose or vaporize, thereby ensuring the stability of the separation process. Ethanol and water have different boiling points. Under reduced pressure conditions, a temperature of 60-70°C can effectively separate them. Selecting a lower temperature helps save energy and reduce operating costs.
[0067] The organic amine compound described in step (1) is 0.82-1.63 g; the value of 0.82-1.63 g of the organic amine can ensure the completeness of the reaction, and sufficient organic amine can ensure sufficient reaction with piperazine to generate the desired product; at the same time, excessive amine can be avoided to cause complicated subsequent treatment. Under the premise of ensuring the reaction efficiency, the experimental cost can be controlled by adjusting the amount of amine to avoid unnecessary waste. Piperazine is 0.68-2.05 g to ensure matching with the value range of the organic amine compound, so that the two can fully contact and react in the reaction; by controlling the amount of piperazine, the influence of unreacted piperazine on the purity of the product can be reduced. Ethanol as a solvent can dissolve the reactants and promote the reaction. The value range of 16-40 g of ethanol ensures a sufficient solvent environment so that the reactants can be fully mixed; water as another solvent can make up for the deficiencies of ethanol, such as solubility or reaction activity; the ratio of ethanol to water is controlled within the range of 4:1, which helps to remove impurities that have not reacted completely during the rotary evaporation and drying process and improve the purity of the product.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] 1. In the present application, hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst work together to increase the absorption amount, absorption rate, desorption rate and desorption amount, and reduce energy consumption; and the present application has good recycling performance, and the raw materials and synthesis process are simple. AEEA reacts with carbon dioxide to form carbamate, and [DETAH][Pz] and AEEA work synergistically to delay the consumption of AEEA and increase the overall carbon dioxide absorption, making its absorption rate fast. The main amine group of AEEA reacts first, providing an initial absorption rate, while [DETAH][Pz] alleviates the decrease in absorption rate through subsequent reactions, and promotes the hydrolysis of carbamate to form carbonate and bicarbonate, thereby improving the absorption capacity.
[0070] During the carbon dioxide absorption process, the Bronsted acid sites on the catalyst surface act as proton donors. Under the action of protons, the carbonyl carbon atom of the carboxylate ion in the zwitterion is attacked, resulting in the rupture of the carbon-nitrogen bond, and then the formation of carboxylic acid and amine compounds, converting the unstable carbamate intermediate product into a more stable carboxylic acid product, while releasing amine compounds, promoting the process of carbon dioxide absorption. During the carbon dioxide desorption process, the BASs of the catalyst provide protons H + , promoting urethane RN + -COO - The proton also passes through the active site B of BASs. - From the protonated amine RNH3 + The protons in the piperazine anion accelerate the deprotonation process; the protonated piperazine anion promotes the RN + -COO - decomposition, while ensuring that AEEA and [DETAH] + regeneration.
[0071] 2. The low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent of the present invention has the advantages of low viscosity and low density. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 This is a diagram of a carbon dioxide absorption device.
[0073] Figure 2 This is a diagram of the carbon dioxide desorption device.
[0074] Figure 3 Graphs showing the carbon dioxide desorption amount and desorption rate of Examples 1 to 11.
[0075] Figure 4 Graphs showing the carbon dioxide desorption amount and desorption rate of Examples 12 to 20.
[0076] Figure 5 It is a graph of the carbon dioxide desorption amount and desorption rate of Comparative Example 3, Example 7 and Examples 21 to 23.
[0077] Figure 6 This is a graph showing the carbon dioxide desorption amount and desorption rate for the comparative example.
[0078] Figure 7 This is the absorption-desorption diagram of carbon dioxide for 5 cycles in Example 7.
[0079] Figure 8 This is a color change diagram of carbon dioxide in Example 7 without carbon dioxide absorption, after absorbing carbon dioxide 5 times, and after desorbing carbon dioxide 5 times.
[0080] Fig. 9 for13 CNMR spectrum.
[0081] Fig.10 This is a graph showing the changes in viscosity and density after carbon dioxide absorption in Examples 1, 2 and 7 and before carbon dioxide absorption in Example 7.
[0082] Fig.11 It is a comparison chart of 30% EMA regeneration energy consumption in comparative example 1, embodiment 7 and background technology.
[0083] Fig.12 This is a scanning electron micrograph of H-ZSM-5(21).
[0084] Fig.13 This is the energy spectrum analysis diagram of H-ZSM-5(21). DETAILED DESCRIPTION
[0085] The present invention will be further described below with reference to specific embodiments and comparative examples.
[0086] Embodiment 7 is the best embodiment of the present invention. The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0087] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows:
[0088] Diethylenetriamine: chemically pure, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Piperazine: piperazine is anhydrous piperazine, chemically pure, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ethanol: ethanol is anhydrous ethanol, chemically pure, purchased from Sinopharm Chemical Reagent Co., Ltd.; Hydroxyethylethylenediamine: Hydroxyethylethylenediamine is N-(2-hydroxyethyl)ethylenediamine, chemically pure, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ethanolamine: Ethanolamine is referred to as MEA; chemically pure, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Nano-dioxygen Silicon dioxide: chemically pure, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; Nano-titanium dioxide: chemically pure, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; Activated carbon: chemically pure, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; H-MOR: H-MOR is Mordenite, with a silicon-aluminum ratio of 25, chemically pure, purchased from Tianjin Nanhua Catalyst Co., Ltd.; SAPO-34: with a silicon-aluminum ratio of 0.5, chemically pure, purchased from Tianjin Nanhua Catalyst Co., Ltd.; HY: with a silicon-aluminum ratio of 80, chemically pure, purchased from Tianjin Tianjin Nanhua Catalyst Co., Ltd.; H-ZSM-5 is ZSM-5; H-ZSM-5 (21): silicon-aluminum ratio is 21, chemically pure, purchased from Tianjin Nanhua Catalyst Co., Ltd.; H-ZSM-5 (27): silicon-aluminum ratio is 27, chemically pure, purchased from Tianjin Nanhua Catalyst Co., Ltd.; H-ZSM-5 (46): silicon-aluminum ratio is 46, chemically pure, purchased from Tianjin Nanhua Catalyst Co., Ltd.; water is distilled water; vacuum drying oven is DZF-6020 vacuum drying oven, purchased from Shanghai Jinghong Experimental Equipment Co., Ltd.; vacuum pump The vacuum pump is a 2XZ-2 rotary vane vacuum pump purchased from Linhai Tanshi Vacuum Equipment Co., Ltd.; the ultrasonic cleaning machine is an LC-UC-220 ultrasonic cleaning machine purchased from Shanghai Lichen Bangxi Instrument Technology Co., Ltd.; the rotary evaporator is an R1001-VN rotary evaporator purchased from Zhengzhou Great Wall Science and Technology Co., Ltd.; the viscometer is an NDJ-5S digital viscometer purchased from Deka Precision Measuring Instrument (Shenzhen) Co., Ltd.; the density meter is an AR-120Y density meter purchased from Shenzhen Dahong Meituo Density Measurement Instrument Co., Ltd.; the spectrometer is a 13 C NMR spectrometer, Bruker Avance III HD 600MHz; calorimeter: Calvet calorimeter, Setaram C600; scanning electron microscopy and energy spectrum analysis combined test using SEM-EDS technology, Gemini SEM500.
[0089] Example 1
[0090] A method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent; comprising the following steps:
[0091] (1) 2.45 g of diethylenetriamine, 2.05 g of piperazine, 40 g of ethanol and 10 g of water were reacted under magnetic stirring at a temperature of 40° C. and a rotation speed of 800 rpm for 36 hours to obtain component A;
[0092] (2) distilling component A under reduced pressure at 70° C. for 3.5 h to constant weight, using a rotary evaporator for reduced pressure distillation, and drying in a vacuum drying oven for 12 h to obtain an amino-functionalized ionic liquid;
[0093] (3) 4.5 g of the amino-functionalized ionic liquid obtained in step (2), 4.5 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (21) and 20.97 g of water were mixed and ultrasonically dispersed for 10 min, and an ultrasonic cleaning machine was used to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent, wherein the proportion of each component was: 15 wt% AEEA + 15 wt% [DETAH] [Pz] + 0.01 wt% H-ZSM-5 (21);
[0094] Absorption process: put 30g of the prepared low-energy and high-efficiency synergistic carbon dioxide absorbent into the bubbling absorption tube, and place the bubbling absorption tube in a constant temperature oil bath at 40℃; after the temperature of the compound solution stabilizes, open the valve of the CO2 gas cylinder, adjust the pressure reducing valve to control the inlet pressure at 0.1MPa, and the mass flow meter can control the inlet volume at 150g / min. Use a wet flow meter to detect the amount of CO2 in the outlet gas of the bubbling absorption tube in real time, and record the data every 2 minutes. When the difference between the inlet and outlet flow rates is less than 5g / min, it is considered that the absorption has reached saturation and the test is stopped; for the absorption device, see Figure 1 ;
[0095] Desorption process: Place the bubbling absorption tube filled with the saturated ionic liquid solution-organic amine composite solution in a constant temperature oil bath at 130°C, connect the serpentine condenser, and regenerate it by normal pressure heating. Read the amount of CO2 desorbed from the solution through a wet flow meter; record the data every 2 minutes. Stop the experiment after the wet flow meter stops rotating. See the desorption device for details. Figure 2 ;
[0096] The absorption-desorption devices used in this application are the same as those in Example 1.
[0097] Example 2
[0098] A method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent; comprising the following steps:
[0099] 1) 0.82 g of diethylenetriamine, 0.68 g of piperazine, 16 g of ethanol and 4 g of water were reacted at 25° C. and 400 rpm with magnetic stirring for 12 h to obtain component A;
[0100] (2) distilling component A under reduced pressure at 60° C. for 2.5 h to constant weight, using a rotary evaporator for reduced pressure distillation, and drying in a vacuum drying oven for 8 h to obtain an amino-functionalized ionic liquid;
[0101] (3) 1.5 g of the amino-functionalized ionic liquid obtained in step (2), 7.5 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (21) and 20.97 g of water were mixed and ultrasonically dispersed for 6 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 25 wt% AEEA + 5 wt% [DETAH] [Pz] + 0.01 wt% H-ZSM-5 (21).
[0102] Example 3
[0103] A method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent; comprising the following steps:
[0104] (1) 1.63 g of diethylenetriamine, 1.37 g of piperazine, 32 g of ethanol and 8 g of water were reacted at a temperature of 30° C. and a rotation speed of 600 rpm for 24 hours to obtain component A;
[0105] (2) distilling component A under reduced pressure at 65° C. for 3 h to constant weight, using a rotary evaporator for reduced pressure distillation, and drying in a vacuum drying oven for 10 h to obtain an amino-functionalized ionic liquid;
[0106] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of nano-silicon dioxide and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% SiO2.
[0107] Example 4
[0108] The difference from Example 3 is step (3):
[0109] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of nano-titanium dioxide and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was used to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH][Pz] + 0.01 wt% TiO2.
[0110] Example 5
[0111] The difference from Example 3 is step (3):
[0112] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of AC and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% AC.
[0113] Example 6
[0114] The difference from Example 3 is step (3):
[0115] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-MOR and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH][Pz] + 0.01 wt% H-MOR.
[0116] Example 7
[0117] The difference from Example 3 is step (3):
[0118] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (21) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% H-ZSM-5 (21).
[0119] Example 8
[0120] The difference from Example 3 is step (3):
[0121] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (46) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% H-ZSM-5 (46).
[0122] Example 9
[0123] The difference from Example 3 is step (3):
[0124] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (27) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% H-ZSM-5 (27).
[0125] Example 10
[0126] The difference from Example 3 is step (3):
[0127] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of HY and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% HY.
[0128] Embodiment 11
[0129] The difference from Example 3 is step (3):
[0130] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of SAPO-34 and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% SAPO-34.
[0131] Example 12
[0132] A method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent; comprising the following steps:
[0133] (1) 1.89 g of triethylenetetramine, 1.11 g of piperazine, 32 g of ethanol and 8 g of water were reacted at a temperature of 30° C. and a rotation speed of 600 rpm for 24 hours to obtain component A;
[0134] (2) distilling component A under reduced pressure at 65° C. for 3 h to constant weight, using a rotary evaporator for reduced pressure distillation, and drying in a vacuum drying oven for 10 h to obtain an amino-functionalized ionic liquid;
[0135] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of nano-silicon dioxide and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.01 wt% SiO2.
[0136] Example 13
[0137] The difference from Example 12 is step (3):
[0138] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of nano-titanium dioxide and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% TiO2.
[0139] Embodiment 14
[0140] The difference from Example 12 is step (3):
[0141] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of AC and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% AC.
[0142] Embodiment 15
[0143] The difference from Example 12 is step (3):
[0144] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-MOR and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH][Pz] + 0.01 wt% H-MOR.
[0145] Example 16
[0146] The difference from Example 12 is step (3):
[0147] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (21) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% H-ZSM-5 (21).
[0148] Embodiment 17
[0149] The difference from Example 12 is that in step (3) of this example:
[0150] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (46) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% H-ZSM-5 (46).
[0151] Embodiment 18
[0152] The difference from Example 12 is step (3):
[0153] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of H-ZSM-5 (27) and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% H-ZSM-5 (27).
[0154] Embodiment 19
[0155] The difference from Example 12 is that in step (3) of this example:
[0156] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of HY and 20.97 g of water were mixed and ultrasonically dispersed for 8 min. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% HY.
[0157] Embodiment 20
[0158] The difference from Example 12 is step (3):
[0159] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.03 g of SAPO-34 and 20.97 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [TETAH] [Pz] + 0.01 wt% SAPO-34.
[0160] Embodiment 21
[0161] The same as Example 7 is step (3):
[0162] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.015 g of H-ZSM-5 (21) and 20.985 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.005 wt% H-ZSM-5 (21).
[0163] Embodiment 22
[0164] The same as Example 7 is step (3):
[0165] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.045 g of H-ZSM-5 (21) and 20.955 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.015 wt% H-ZSM-5 (21).
[0166] Embodiment 23
[0167] The same as Example 7 is step (3):
[0168] (3) 3 g of the amino-functionalized ionic liquid obtained in step (2), 6 g of hydroxyethylethylenediamine, 0.06 g of H-ZSM-5 (21) and 20.94 g of water were mixed and ultrasonically dispersed for 8 minutes. Ultrasonic cleaning was performed using an ultrasonic cleaning machine to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorbent. The proportion of each component was: 20 wt% AEEA + 10 wt% [DETAH] [Pz] + 0.02 wt% H-ZSM-5 (21).
[0169] Comparative Example 1
[0170] This comparative example is a mixed solution of 9 g of ethanolamine and 21 g of water.
[0171] Comparative Example 2
[0172] This comparative example is a mixed solution of 9 g of hydroxyethylethylenediamine and 21 g of water.
[0173] Comparative Example 3
[0174] The preparation method of the low-energy consumption and high-efficiency synergistic carbon dioxide absorber described in this comparative example is the same as that in Example 7, the only difference is that 0 parts of catalyst are added in step (3).
[0175] Comparative Example 4
[0176] The preparation method of the low-energy consumption and high-efficiency synergistic carbon dioxide absorber described in this comparative example is the same as that in Example 12, with the only difference being that 0 parts of catalyst is added in step (3).
[0177] Performance Testing
[0178] The performance test of the low energy consumption and high efficiency synergistic carbon dioxide absorbent prepared in the examples and comparative examples is carried out. The specific test results are shown in Figures 3 to 13 and Table 1.
[0179] Viscosity test: Use a digital viscometer to measure the viscosity of the low-energy, high-efficiency, synergistic carbon dioxide absorbent before and after absorption. Estimate the measured viscosity value and determine the test rotor for testing. Place a certain amount of low-energy, high-efficiency, synergistic carbon dioxide absorbent in the instrument, use the viscometer to measure continuously for 3 times and take the average value as the final viscosity value. When testing the viscosity at high temperature, place the instrument containing the absorbent solution in a water bath and keep it warm to the test temperature before measuring.
[0180] Density test: Use a densitometer to measure the density of the low-energy and high-efficiency synergistic carbon dioxide absorbent before and after absorbing carbon dioxide. The average value of three measurements is taken as the density of the absorbent.
[0181] 13 CNMR: Sample preparation: Use a clean and dry sample tube, take a small amount of low-energy consumption and high-efficiency synergistic carbon dioxide absorber and put it into the sample tube, add 0.5mL of deuterated solvent, and shake to dissolve the sample. Use a height gauge to determine the placement height of the sample to be measured; use 13 C NMR spectrometer, Bruker Avance III HD 600 MHz.
[0182] Calorimetric test: Sample preparation: Place the low-energy and high-efficiency synergistic carbon dioxide absorber to be tested in the sample cell of the calorimeter, and ensure that the sample cell is well sealed to reduce heat loss; use Calvet calorimeter, Setaram C600.
[0183] Scanning electron microscopy and energy spectrum analysis test: sample preparation, fix the low-energy and high-efficiency synergistic carbon dioxide absorber to be observed on a suitable film; use SEM-EDS combined detection equipment, Gemini SEM 500.
[0184] Table 1 Element content results of H-ZSM-5(21) by energy spectrum analysis.
[0185]
[0186] The absorption amount of Examples 1 to 23 is 0.52 g CO2·g -1 Amine~0.58g CO2·g -1 Amine; wherein Example 7 has the best absorption capacity of 0.58g CO2·g -1 Amines; In actual industrial applications, organic amine absorption systems cannot achieve complete carbon dioxide desorption. The carbon dioxide desorption performance in the first 20 minutes of the regeneration process is an important reference indicator for evaluating the carbon dioxide capture efficiency. 0.1wt% of 9 catalysts were added to the 20wt% AEEA + 10wt% [DETAH][Pz] composite system to compare the entire desorption process and the changes in desorption amount and desorption rate in the first 20 minutes.
[0187] The desorption performance in the first 20 minutes showed that the system with added catalyst was significantly better than the non-catalytic process in terms of carbon dioxide desorption amount, average desorption rate and peak desorption rate. Figure 3 and Figure 6 It can be seen that the desorption amount and average rate in the first 20 minutes are as follows: Example 7> Example 6> Example 8> Example 9> Example 5> Example 4> Example 3> Example 10> Example 11> Comparative Example 3; No catalyst was added to Comparative Example 3. Example 7 showed the best desorption performance within 20 minutes, and the desorption amount of Example 7 reached 0.1369g CO2·g -1 Amine, comparative example 3 desorbed 0.0841 gCO2·g in 20 minutes -1 Amine, Example 7 is 62.78% higher than Comparative Example 3. The average desorption rate is from 0.00590 g CO2·g -1 Amine min -1 Increased to 0.00831 g CO2 g -1 Amine min -1 , an increase of 40.85%; the peak desorption rate increased from 0.01584g CO2·g -1 Amine min -1 Increased to 0.0209 g CO2 g -1 Amine min -1, an increase of 31.94%. It can be seen that the addition of catalyst increases the CO2 desorption amount, desorption amount and desorption rate.
[0188] Depend on Figure 3 and Figure 4 It can be seen that Example 7 has the best desorption performance; the low energy consumption and high efficiency synergistic carbon dioxide absorbent obtained in Example 7 was subjected to five absorption-desorption cycle performance tests under specific conditions. Figure 7 It can be seen that the first carbon dioxide absorption is 0.50172g CO2·g -1 After 5 regeneration cycles, the carbon dioxide absorption of the solution was 0.42619 g CO2 g -1 Amine maintained 84.95% of the first absorption amount, reached a stable carbon dioxide absorption and desorption amount after the first carbon dioxide absorption-desorption cycle, and the absorption and desorption amount remained basically stable after five cycles. It can be seen that the present application has good stability.
[0189] Depend on Figure 8 It can be seen that the low-energy consumption and high-efficiency synergistic carbon dioxide absorber obtained in Example 7 has little color change before absorbing carbon dioxide, after 5 absorptions and after 5 desorptions, indicating that the low-energy consumption and high-efficiency synergistic carbon dioxide absorber obtained in Example 7 is relatively stable and has a high desorption rate.
[0190] Depend on Figure 3 , Figure 4 and Figure 5 It can be seen that when the proportion of added catalyst is 0.01wt%, the best desorption amount and desorption rate are achieved.
[0191] The addition of catalyst mainly enhanced the desorption performance within the first 20 min, therefore, the desorption amount and desorption rate within the first 20 min were used as key evaluation indicators to assess the effect of catalyst on the desorption performance.
[0192] Depend on Figure 5 It can be seen that with the increase in the amount of H-ZSM-5 (21) added, the desorption amount and the desorption amount in the first 20 minutes both showed a trend of first increasing and then decreasing; under the catalyst addition amounts of Example 22 and Example 7, the desorption amount was not much different. However, in the first 20 minutes, Example 7 showed a higher peak desorption rate and average desorption rate, indicating that the addition amount of 0.1wt% has the best catalytic effect on the CO2 desorption process at this stage.
[0193] Depend on Figure 6 It can be seen that the saturated absorption amounts of Comparative Examples 3 and 4 are 0.45-0.47 g CO2·g -1 Amine and 0.50~0.52g CO2·g -1Amine, are better than Comparative Example 1 and Comparative Example 2. Comparative Example 3 has a better absorption effect than other comparative examples. Comparative Example 3 is the patent named in the background technology as a composite absorbent of amino-functionalized ionic liquid-alcoholamine for CO2 capture and its preparation method, which discloses a composite absorbent prepared from main absorbent alcoholamine, absorption promoter amino-functionalized ionic liquid and water, but its energy consumption is high, the desorption rate is low, and the system does not have the synergistic effect of hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst. The desorption amount and desorption rate of Comparative Examples 3 and 4 are lower than those of Example 7 and Example 12. It can be seen that hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst synergize to improve the desorption rate and desorption amount. One of the three is used as an absorbent alone or two of them are mixed. It is impossible to achieve the effect that can be achieved by this application.
[0194] exist Fig. 9 In (a) and (b), when the low-energy-consumption and high-efficiency synergistic carbon dioxide absorber does not react with carbon dioxide, that is, La = 0, the high-field region of the nuclear magnetic resonance spectrum only shows 7 characteristic peaks of AEEA and [DETAH][Pz]. When the carbon dioxide absorption increases from 0 to La = 0.31 g CO2·g -1 When amine was reacted, three new peaks appeared in the chemical shift range of 56-61ppm, 49-50ppm and 46-48ppm in the high field region. These peaks are the characteristic peaks of C atoms in the carbamate formed by the reaction of AEEA and carbon dioxide. Among them, the C1′-C4′ and C8 peaks are the carbamate formed by the reaction of AEEA primary amine group and carbon dioxide, while the C1′-C4′ and C9 peaks represent the carbamate formed by AEEA secondary amine group. At the same time, two peaks appeared at 164.51 and 164.61ppm in the low field region, further confirming the formation of carbamate.
[0195] Carbon dioxide absorption increased to La = 0.46 g CO2 g -1 Amine, four new peaks appeared in the high field region at chemical shifts of 45.62 and 45.24 ppm, 39.07 and 38.73 ppm, which are caused by [DETAH] + The peak of carbamate formed by reaction with carbon dioxide. At this time, [DETAH] + It begins to participate in the reaction of carbon dioxide, alleviating the problem of decreased absorption rate caused by the consumption of amine in the solution.
[0196] When the carbon dioxide absorption of the solution increases again to La = 0.50 g CO2 g -1 When amine was present, the signals of C8 and C10 peaks were significantly enhanced, which indicated that AEEA and [DETAH] +All of them react with carbon dioxide at the same time. When the solution reaches the final saturation state, La = 0.5g CO2·g -1 When amine is present, the solution contains both the primary amine and the secondary amine of AEEA to form carbamate, [DETAH] + The generated carbamate, carbonate and bicarbonate. The chemical shift of the resonance peak corresponding to C7 of [Pz] changed from δ = 44.79 ppm to δ = 42.55 ppm, confirming that [Pz] was protonated during the absorption of carbon dioxide in the solution.
[0197] During the carbon dioxide absorption process, the Bronsted acid sites on the catalyst surface act as proton donors. Under the action of protons, the carbonyl carbon atom of the carboxylate ion in the zwitterion is attacked, resulting in the rupture of the carbon-nitrogen bond, and then the formation of carboxylic acid and amine compounds, converting the unstable carbamate intermediate product into a more stable carboxylic acid product, while releasing amine compounds, promoting the process of carbon dioxide absorption. During the carbon dioxide desorption process, the BASs of the catalyst provide protons H + , promoting urethane RN + -COO - The proton also passes through the active site B of BASs. - From the protonated amine RNH3 + The protons in the piperazine anion accelerate the deprotonation process; the protonated piperazine anion promotes the RN + -COO - decomposition, while ensuring that AEEA and [DETAH] + regeneration.
[0198] Depend on Fig.10 It can be seen that within the temperature range of 30 to 90°C, Fig.10 The viscosity of the four absorbents changes linearly with temperature, specifically, the viscosity decreases with increasing temperature. In particular, at 30°C, the viscosity of the low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent obtained in Example 7 before and after carbon dioxide absorption is 4.2 mPa·s and 5.8 mPa·s, respectively, which is significantly lower than the viscosity of the ionic liquid absorption system used previously.
[0199] also, Fig.10 The density of the four absorbents in the solution showed a strong temperature dependence, and the density decreased with increasing temperature. This phenomenon is attributed to the increase in the average kinetic energy of the molecules in the solution after heating, which weakened the interaction between molecules and increased the average distance between molecules, thereby reducing the number of molecules per unit volume and ultimately leading to a decrease in density.
[0200] In summary, the low-energy consumption and high-efficiency synergistic carbon dioxide absorbent obtained in Example 7 exhibits relatively low viscosity and relatively low density before and after absorbing CO2. This phenomenon indicates that the low-energy consumption and high-efficiency synergistic carbon dioxide absorbent has a low mass transfer resistance between the liquid and gas phases, which promotes the efficient diffusion of carbon dioxide in the absorption system.
[0201] Depend on Fig.12 It can be seen that the low-energy consumption and high-efficiency synergistic carbon dioxide absorbent obtained in Example 7 has low energy consumption during the regeneration process, mainly due to the reaction heat Q des , latent heat Q latent and sensible heat Q sen Compared with Comparative Example 1, the regeneration energy consumption of Example 7 is reduced by 30.22%. The maximum energy composition Q of the low energy consumption and high efficiency synergistic carbon dioxide absorbent obtained in Example 7 is des The desorption heat reduction of Example 7 is 1.27 GJ / tCO2, which is 32.09% lower than 1.87 GJ / tCO2 of Comparative Example 1. The reduction of the desorption reaction heat of Example 7 is attributed to the synergistic effect of the [DETAH][Pz] ionic liquid and the catalyst. The BAS and [Pz] - As a proton donor, LAS acts as an electron acceptor, which effectively promotes the decomposition of carbamate, reduces the reaction energy barrier, optimizes the reaction path, and thus reduces the desorption reaction heat.
[0202] In addition, the low energy consumption and high efficiency synergistic carbon dioxide absorbent obtained in Example 7 has a Q sen The total heat of the CO2 absorption solution was 0.74 GJ / tCO2, which was 14.94% lower than that of 0.87 GJ / tCO2 in Comparative Example 1. This reduction was mainly attributed to the lower specific heat of AEEA and [DETAH][Pz] in Example 7 compared with the traditional amine solution, which reduced the overall specific heat of the CO2 absorption solution. In addition, the Q of the low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent obtained in Example 7 was latent It is 0.83 GJ / tCO2, which is 37.59% lower than 1.33 GJ / tCO2 of Comparative Example 1; the reduction is attributed to the non-volatile nature of [DETAH][Pz], which reduces the vapor pressure of the solution, thereby reducing the amount of water evaporated in the reboiler, greatly reducing the latent heat of evaporation during the desorption process.
[0203] The crystal structure of H-ZSM-5(21) is composed of silicon, aluminum and oxygen tetrahedrons as basic units. These tetrahedrons are further combined to form silicon-aluminum five-membered rings, and eight of these five-membered rings together constitute the core structural unit of H-ZSM-5(21). The morphological characteristics of H-ZSM-5(21) were observed using high-resolution scanning electron microscopy, such as Fig.12As shown in the scanning electron microscope image, H-ZSM-5 (21) crystals have clear crystallographic morphology, including block, columnar and prismatic structures. The overall morphology and crystal size are relatively complete, indicating a high degree of crystallinity. The crystal particles stack on each other to form larger irregular aggregates, which are further connected into clusters; the stacking of aggregates shows a certain degree of layered structure between crystals.
[0204] This structural feature forms a large number of pores between the particles, indicating that H-ZSM-5(21) has a large specific surface area and excellent pore structure, making it very suitable for the catalytic desorption process of carbon dioxide.
[0205] In order to understand the elemental composition and distribution characteristics of H-ZSM-5(21), energy spectrum analysis was used for detailed characterization, such as Fig.13 As shown, Fig.13 (a) is the scanning area. Fig.13 In (b), the cyan element distribution map clearly shows the distribution of Si in the sample. The Si element is highly evenly distributed in the sample area, indicating that Si is evenly integrated into the H-ZSM-5(21) framework, forming a stable structural foundation.
[0206] exist Fig.13 In (c), the blue element distribution map shows the distribution of Al element. Compared with the uniform distribution of Si, the distribution of Al is more dispersed, and some isolated points show higher intensity. This unique distribution pattern indicates that Al is embedded in the zeolite structure in the form of isolated points or clusters, thereby enhancing its catalytic activity.
[0207] exist Fig.13 In (d), the green element distribution diagram shows the distribution of O. Similar to Si, O also shows a relatively uniform distribution, which further confirms that O has been integrated into the H-ZSM-5(21) structure, forming Si-O and Al-O bonds with Si and Al atoms, thus constructing the basic framework of zeolite.
[0208] Table 1 shows the precise calculation and analysis of the Si, Al and O contents in the H-ZSM-5 (21) catalyst by energy spectrum analysis elemental analysis. The atomic percentage of O is as high as 63.93%, highlighting the important role of O in HZSM-5 zeolite. O, Si and Al form a skeleton structure together. At the same time, the mass ratio of Si to Al is 16.08, and the atomic ratio is 15.4, which is highly consistent with the H-ZSM-5 (21) silicon-aluminum ratio of 21, further verifying the rationality and stability of the catalyst structure. .
[0209] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A low energy consumption and high efficiency synergistic carbon dioxide absorbent, characterized in that: The invention comprises the following components: 4.5-7.5 g of hydroxyethylethylenediamine, 1.5-4.5 g of amino-functionalized ionic liquid, 0.015-0.06 g of catalyst and water.
2. A low energy consumption and high efficiency synergistic carbon dioxide absorbent according to claim 1, characterized in that: The weight percentages of the hydroxyethylethylenediamine, amino-functionalized ionic liquid and catalyst are 15-25%: 5-15%: 0.005-0.02%.
3. A low energy consumption and high efficiency synergistic carbon dioxide absorbent according to claim 1, characterized in that: The catalyst is nano silicon dioxide, nano titanium dioxide, activated carbon or zeolite molecular sieve.
4. A low energy consumption and high efficiency synergistic carbon dioxide absorbent according to claim 1, characterized in that: The catalyst is a zeolite molecular sieve with a silicon-aluminum ratio of 0.5-80.
5. A low energy consumption and high efficiency synergistic carbon dioxide absorbent according to claim 1, characterized in that: The catalyst is H-MOR, H-ZSM-5, HY or SAPO-34 zeolite molecular sieve.
6. The method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) reacting 0.82-2.45 g of an organic amine compound, 0.68-2.05 g of piperazine, 16-40 g of ethanol and 4-10 g of water to obtain component A; (2) distilling component A under reduced pressure and drying to obtain an amino-functionalized ionic liquid; (3) The amino-functionalized ionic liquid obtained in step (2), hydroxyethylethylenediamine, a catalyst and water are mixed and ultrasonically dispersed to obtain a low-energy consumption and high-efficiency synergistic carbon dioxide absorber.
7. The method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent according to claim 6, characterized in that: The organic amine compound is diethylenetriamine or triethylenetetramine.
8. The method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent according to claim 6, characterized in that: The temperature of the reduced pressure distillation is 60-70°C, and the time of the reduced pressure distillation is 3-4h.
9. The method for preparing a low-energy-consumption and high-efficiency synergistic carbon dioxide absorbent according to claim 6, characterized in that: 0.82-1.89 g of the organic amine compound described in step (1).
Citation Information
Patent Citations
Multi-amino functionalized ionic liquid as well as preparation method and application thereof
CN115945034A
Amino-functionalized ionic liquid-alcohol amine compound absorbent for CO2 capture and preparation method of amino-functionalized ionic liquid-alcohol amine compound absorbent
CN119258727A
Cited By
Nanoparticle enhanced functionalized ionic liquid liquid-liquid phase change absorbent as well as preparation method and application thereof
CN121082057A